From the EU Refugee Crisis to the Next-Door Refugee: 'Saving' Refugees in Portugal. - Padilla, B.; Goldberg, A.; Vieira, A. (European Consortium for Political Research (ECPR) 2019 General Conference, 2019)
Historically, Portugal had received a very small numbers of refugees, however since the so-called “Refugee crisis”, with the pressure the EU for a common policy to face the crisis, it has become a new destination for the refugees, primarily through the EU relocation programme and secondarily from the UNRC reinstallation programme. In a short period of time, between 2016 and 2017, Portugal received over 1.500 refugees. This shift had an impact at the policy-level as well as in civil society, as both reorganized to face the challenges. On the one hand, changes were implemented with regards to who is responsible for overseeing and implementing refugees’ policies, and on the other, civil society with no previous extensive experience in the field of refugees (or even migration) jumped into taking over reception programmes for this population. Within the state, in addition to the central government, municipalities also decided to host refugees, creating a complex governance structure. Overall, the National Programme for the Reception and Integration of Refugees was created, and a model of collaboration with the participation of civil society organizations and municipalities was designed, based on a decentralized model. The programme, with a duration of 18 month (or 24 for families) offered support through municipalities or/and civil society organizations, giving a monthly subsidy, housing, language training, labour market integration and health services. As this programme ended, it is relevant to assess its strengths and weaknesses. In this paper, we offer an assessment based on ethnographic work (interviews with key actors, in-depth interviews with male and female refugees, and participant observation), tot capture their reality and experience in Portugal, from the perspective of the involved actors, with the purpose of drawing practical conclusions and learning lessons for future policies.